Upaya Meningkatkan Efektivitas Belajar Siswa melalui Pendekatan Open Ended Learning dalam Mata Pelajaran Fiqih Kelas X di MA Hidayatul Mubtadiin Lampung Selatan - Sella Assri Saputri; Mujiatun Mujiatun; Ami Latifah (Departement of Mathematics Education, 2023)
This study aims to analyze efforts to increase student learning effectiveness through the Open Ended Learning approach in the subject of Fiqh in class X at MA Hidayatul Mubtadiin. The research method used is descriptive qualitative with data collection through observation, interviews, and documentation. The results of the research show that the Open Ended Learning approach is effective in improving the learning of Fiqh in class X IIS. Students are actively engaged, improving conceptual understanding and critical thinking skills. Supporting factors include teacher alignment, use of relevant learning resources, and active student participation. Inhibiting factors include the teacher's lack of understanding, limited resources, and school support.